Structural Design and Training Planning for Ankle Rehabilitation Mechanisms - Li Jingjing; Han Chunyang; Xu Zhenbang (Jixie chuandong)
In order to ensure the effectiveness and safety of ankle rehabilitation training, an ankle rehabilitation mechanism based on the 3-UPRU/S parallel configuration and its foot fixation and quick release components are designed, and its motion performance and training planning are investigated. A virtual model of the rehabilitation mechanism is established using Adams software. Taking into account the influence of the non-coincidence between the physiological center of the rotation of the ankle joint and the center of the rotation of the mechanism, the virtual model of the ankle is introduced and the S-shaped and T-shaped angular velocity curves are optimized using angular velocity planning to obtain a better training plan. The displacement data of each actuator of the mechanism is obtained by inverse kinematic simulation, and the drive function of each actuator is determined using spline fitting. The actual working angle and training plan are verified by means of a principle prototype test. The results show that the optimized mechanism can increase the training time at constant speed by approximately 12% and reduce the angular velocity fluctuations by approximately 47% in one cycle, indicating that the training plan can improve the effectiveness and safety of the ankle rehabilitation.